1993
DOI: 10.1002/path.1711700212
|View full text |Cite
|
Sign up to set email alerts
|

Expression of proliferating cell nuclear antigen (PCNA) in dysplasia of the bronchial epithelium

Abstract: Proliferating cell nuclear antigen (PCNA) is expressed in cells in the cell cycle and has been studied as a marker of proliferation in lung and other tumours. We have noted immunocytochemical differences in PCNA expression between normal and neoplastic bronchial cells. As bronchial dysplasia is considered preneoplastic, we have examined PCNA expression in this condition. PCNA staining in 47 cases of bronchial dysplasia and 32 samples of normal bronchial epithelium was compared. Of the dysplasias, three were mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 13 publications
2
30
0
1
Order By: Relevance
“…We demonstrated that squamous metaplasia in honeycomb lesion has a higher proliferative activity. A significant increase in PCNA count is reported in moderate and severe dysplasia of the bronchial epithelium [29]. The higher PCNA positivity of the hyperplastic epithelium in the honeycomb lesions of IPF indicates that accelerated cell proliferation occurs in these lesions.…”
Section: Discussionmentioning
confidence: 97%
“…We demonstrated that squamous metaplasia in honeycomb lesion has a higher proliferative activity. A significant increase in PCNA count is reported in moderate and severe dysplasia of the bronchial epithelium [29]. The higher PCNA positivity of the hyperplastic epithelium in the honeycomb lesions of IPF indicates that accelerated cell proliferation occurs in these lesions.…”
Section: Discussionmentioning
confidence: 97%
“…Immunostaining for proliferating cell nuclear antigen (PCNA) and Ki67 of the olfactory epithelium allowed to identify the most phases of the cell cycle as was described by Tsuji et al (1992) and Pendleton et al (1993) studying expression of protein markers in human.…”
Section: Pcna and Ki67 Immunostaining Of Cells From Oe Of 60-day Agedmentioning
confidence: 99%
“…O estudo imunohistoquímico foi realizado utilizando téc-nica para marcação do antígeno de proliferação celular (PCNA) que possibilitou a observação desse mecanismo para as célu-las do epitélio olfatório, corroborando com as citações de Tsuji et al (1992) e Pendleton et al (1993) em humanos, para os quais a técnica de imunohistoquímica lança mão de marcadores de proteínas expressas em sua maior parte no ciclo celular. Embora autores como Legrier et al (2001) tenham demonstrado através de marcações positivas para BrdU e PCNA em células do epitélio olfatório de camundongos, que o mecanismo de proliferação celular pode diminuir de 10 a 15 vezes desde o nascimento até os três primeiros meses de idade, ao realizarmos um estudo cego da marcação através de PCNA do epitélio olfatório de cães adultos, não foi verificada diferença quantitativa de marcação entre os indiví-duos dos dois grupos etários estudados, ou entre os sexos.…”
Section: Resul Resul Resul Resul Results T T T Tados E Discus Ados E Dunclassified